Higher load of grapevine buds results in better yield and vegetative vigor indices in ’Cabernet Franc’ grapevine grown in a high-altitude region - Würz, Douglas André; Bonin, Bruno Farias; Brighenti, Alberto Fontanella; Canossa, Adrielen Tamiris; Reinehr, Juliana; Allebrandt, Ricardo; de Bem, Betina Pereira; Rufato, Leo; Kretzschmar, Aike Anneliese (Revista de Ciências Agroveterinárias, 2020)
To reach an adequate vegetative-productive balance, this work aimed to evaluate the effect of an increase of the bud load.plant-1 during pruning, on the productive characteristics and vegetative balance of Cabernet Franc grapevine cultivated in a high-altitude region of the state of Santa Catarina, Brazil. The present work was conducted during the 2016/2017 harvest, in a commercial vineyard located in the municipality of São Joaquim. Cabernet Franc variety grapevines grafted on the ’Paulsen 1103’ rootstock were used. The treatments consisted of four different levels of bud loads: 15, 30, 50, and 75 buds.plant-1. At the time of harvesting, productive and vegetative variables were evaluated, and the growth of branches and secondary shoots was evaluated along the grapevine cycle. The experimental design was a randomized block design with four blocks and five plants per plot. The increase of the bud load.plant-1 increased the number of branches and bunches.plant-1, resulting in increased plant production and productivity. The vegetative variables were influenced by the increase of buds.plant-1, with a reduction of the growth of branches and of secondary shoots. The increase of the bud load allowed a better vegetative-productive balance, with the reduction in the weight of pruning, and a Ravaz Index more suitable for the production of quality wines. In vineyards with low productivity and excessive vegetative vigor, the increase of bud load.plant-1 during winter pruning management is recommended.